THE IMPORTANCE OF BALANCE GAMES FOR CHILDREN'S MOTOR DEVELOPMENT (CIPEEX, 2025)
Introduction: Balance games are fundamental in childhood, as they stimulate motor development and contribute to the evolution of mobility, cognition, and social interaction, promoting quality of life. Participation in balance games during childhood is extremely important, as it offers accelerated motor development. Their proper implementation results in positive progress in mobility, social, and cognitive areas, thus enhancing quality of life in all aspects. The relevance of these playful and relaxed activities that promote health presents a new world to children, allowing them to feel freer to learn. Objective: To analyze the influence of balance games on children's motor development, with an emphasis on coordination. Methods: This study was developed through a literature review. Two articles were used, with the inclusion criterion being the theme of the importance of motor development in childhood written in Portuguese, and the exclusion criterion being articles in English. The research was conducted using the keywords “jogos de equilíbrio” (balance games) and “desenvolvimento motor infantil” (children’s motor development). Results: The analyzed studies indicate that this process is directly linked to physical growth and the stimulation opportunities offered to the child. Motor development is an essential part of child growth, as it involves not only physical movement but also cognitive, social, and emotional aspects. The first five years of life are crucial, as the experiences during this period determine the child's progress in relation to future learning. Conclusions:It is concluded that motor development is very important for the healthy formation and growth of the child, beginning in the first months of life and occurring continuously. Education plays a fundamental role in this process by providing an appropriate environment and games that encourage movement, planning activities that naturally foster motor development according to each child’s age, while respecting their physical limits.
Keywords: Game; development; balance; child